Composite filtering medium for removing low-boiling-point organic matters and preparation method of composite filtering medium

By using the composite layer structure of modified activated carbon particles and activated carbon fibers in the air filter media in the semiconductor manufacturing workshop, the problem of difficult removal of low-boiling organic matter in the prior art is solved, and the efficient adsorption effect of low-boiling and high-boiling organic matter is achieved.

CN119548945APending Publication Date: 2025-03-04HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411959984.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove low-boiling organic matter common in semiconductor manufacturing workshops. Especially when high-boiling organic matter exists, the adsorption effect of low-boiling organic matter is poor, resulting in a short service life.

Method used

A composite filter medium is used, and a modified activated carbon particle adsorption functional layer is provided on the air inlet side, and a modified activated carbon fiber adsorption functional layer is provided on the air outlet side. Activated carbon particles are modified by phosphoric acid and tannin acid, increasing the proportion of mesoporous and macroporous to adsorb high-boiling organic matter; activated carbon fibers are modified by ammonium persulfate and triethylenetetramine to increase microporous to adsorb low-boiling organic matter.

Benefits of technology

It realizes efficient removal of low-boiling organic matter in semiconductor manufacturing workshops, avoids the inhibition of high-boiling organic matter adsorption on low-boiling organic matter, and extends the service life of the filter media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548945A_ABST
    Figure CN119548945A_ABST
Patent Text Reader

Abstract

The invention relates to a composite filter medium for removing low-boiling-point organic matters and a preparation method thereof, the composite filter medium comprises an air inlet side and an air outlet side, the air inlet side is provided with an activated carbon particle adsorption function layer, and the air outlet side adsorption layer is provided with an activated carbon fiber adsorption function layer; the modification method of the active carbon particles comprises the following steps: pre-treating the active carbon particles by using phosphoric acid and tannic acid solutions in sequence, separating and drying, then putting the active carbon particles into an alcoholic solution of a silane coupling agent for dipping modification, and separating and drying to obtain the modified active carbon particles. The modification method of the activated carbon fiber comprises the following steps: treating the activated carbon fiber by using ammonium persulfate, pretreating the activated carbon fiber by using epoxy chloropropane, mixing with an aqueous solution of triethylene tetramine for reaction, separating and drying. The composite filter medium provided by the invention can effectively filter and remove small-molecular organic matters, especially common low-boiling-point organic matters in semiconductor manufacturing FAB air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air purification, and in particular to a composite filter medium for removing low-boiling-point organic matter and a preparation method thereof. Background Art

[0002] In semiconductor manufacturing workshops, the use of low-boiling point organics and high-boiling point organics is very common, mainly used in various process steps such as photolithography, cleaning, etching and deposition. Organic pollutants may have a serious impact on the semiconductor manufacturing process, so with the development of semiconductor manufacturing technology, the control requirements for air molecular contaminants (AMC) are becoming more and more stringent, especially in key processes such as coating and photolithography.

[0003] High-boiling-point organic pollutants (boiling points are usually higher than 100°C) usually refer to organic compounds that can only change from liquid to gas at higher temperatures. Common high-boiling-point organic pollutants in semiconductor manufacturing workshops include various alkanes, alkenes, aromatic compounds (such as toluene, trifluorotoluene, p-xylene, etc.) and ethers. Although high-boiling-point organic matter has low volatility, it is difficult to remove once it is deposited on the wafer surface. Low-boiling-point organic pollutants (boiling points are usually lower than 100°C) are mainly some volatile organic compounds (VOCs). Common low-boiling-point organic matter in semiconductor manufacturing workshops include isopropanol, acetone, ethyl acetate, 1,2-dichloroethane, etc. The organic solvents used in the photolithography process are prone to produce VOCs after volatilization. They have low boiling points, certain polarity and certain lipophilicity, small molecules, fast diffusion speed, and strong penetration. Therefore, the main VOCs with low molecular weight are harmful to human health. The flammability of low-boiling-point organic matter also poses a safety hazard to production.

[0004] In order to remove these low-boiling point organic pollutants, activated carbon membranes are currently mainly used in the industry. Activated carbon membranes are made of activated carbon particles and non-woven fabrics. Their initial efficiency is average, their service life is short at low concentrations, and their efficiency decays quickly. Analysis shows that low-boiling point organic matter is relatively easy to parse out during the activated carbon analysis process, which means that their adsorption force on the activated carbon particles is weak and they are easy to desorb. High-boiling point organic pollutants are more difficult to diffuse in the pore structure of activated carbon due to their large molecular weight and strong intermolecular forces, making them more difficult to parse. At the same time, when mixed organic pollutants with high and low boiling points are on the intake side, the adsorption of VOCs by high-boiling point organic matter is inhibited. For this reason, when using activated carbon particles to adsorb mixed organic pollutants containing high and low boiling points, low-boiling point organic matter is difficult to be adsorbed cleanly, resulting in an extremely short service life. However, in the prior art, few filter membranes are designed specifically based on this characteristic of low-boiling point organic matter and high-boiling point organic matter. For example, Japanese Patent Publication No. JP4589038B2 discloses a filter medium for purifying gas, which uses granular activated carbon, granular zeolite, two layers of non-woven fabrics, adhesives, etc., and is heated in a laminated state to form an activated carbon layer between the two non-woven fabrics. DE10356776B4 discloses an adsorption filter material, including a porous support layer 3 and a porous support layer 5 and an adsorption layer 4 based on activated carbon, which is activated carbon in the form of activated carbon particles and / or activated carbon fibers, and can adsorb chemical toxins. The adsorption layer 4 is discontinuous and is applied to the support layer 3 only in a discontinuous manner by an adhesive.

[0005] In addition, some existing technologies may use activated carbon fibers to filter organic pollutants directly on one side of the airflow. However, when the organic pollutants contain some high-boiling point organic matter, these high-boiling point organic matter will produce adsorption competition, seriously inhibiting or interfering with the adsorption of VOCs by the activated carbon fiber, resulting in poor removal of low-boiling point organic matter in the organic pollutants by the filter assembly. In addition, the microporosity of activated carbon fibers accounts for more than 90%, but the micropore diameter of common activated carbon fiber ACF is still much larger than molecules such as isopropyl alcohol and acetone commonly found in semiconductor manufacturing workshops, resulting in activated carbon fiber ACF being unfavorable for thorough adsorption and purification of low-concentration small molecules. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a composite filter medium for removing low-boiling point organic matter and a preparation method thereof, which solves the technical problem that low-boiling point organic matter in the air of semiconductor manufacturing FAB is difficult to remove.

[0008] (II) Technical solution

[0009] In a first aspect, the present invention provides a method for preparing a composite filter medium for removing low-boiling point organic matter, wherein the composite filter medium comprises an air inlet side adsorption layer and an air outlet side adsorption layer, wherein an activated carbon particle adsorption functional layer is arranged on the air inlet side, and an activated carbon fiber adsorption functional layer is arranged on the air outlet side adsorption layer;

[0010] After the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are prepared respectively, they are compounded to obtain the composite filter medium;

[0011] Among them, in the activated carbon particle adsorption functional layer, the activated carbon particles are modified activated carbon particles, and the modification method of the activated carbon particles is: pre-treating the activated carbon particles with phosphoric acid and tannic acid solutions in sequence, separating and drying, and then putting the activated carbon into an alcohol solution of a silane coupling agent for immersion modification, separating and drying, and obtaining;

[0012] Among them, in the activated carbon fiber adsorption functional layer, the activated carbon fiber is a modified activated carbon fiber, and the modification method of the activated carbon fiber is: using ammonium persulfate to treat the activated carbon fiber, using epichlorohydrin to pretreat the activated carbon fiber, and then mixing the activated carbon fiber with an aqueous solution of triethylenetetramine for reaction, separating, and drying to obtain.

[0013] Activated carbon particles (ACG) are modified by phosphoric acid and tannic acid successively, and a large number of active hydroxyl groups can be grafted. They are further modified by silane coupling agents, so that low polarity (partially hydrophobic) organic coupling groups are grafted onto ACG, which promotes the adsorption of high-boiling-point organic pollutants by ACG. Phosphoric acid is a weak inorganic acid. It is not easy to cause the collapse of the ACG structure after treating ACG, and it can adjust the pore size of ACG so that the proportion of mesopores and macropores on ACG reaches an optimal ratio, which is very beneficial to the adsorption effect of ACG on high-boiling-point organic molecules. Phosphoric acid can connect -P=O- on activated carbon particles and has good chemical connection activity for organic molecules; tannic acid can quickly introduce a large number of phenolic hydroxyl groups and carboxyl groups, and has good antioxidant properties, which can improve the stability and service life of activated carbon.

[0014] The activated carbon fiber (ACF) is first activated with ammonium persulfate to introduce oxygen-containing functional groups such as carboxyl groups, and then modified with epichlorohydrin. After the epichlorohydrin is opened, it is connected to the ACF surface. After that, it is modified with triethylenetetramine, and a large number of amino groups are grafted on the ACF surface. The amino groups are alkaline and are more likely to adsorb low-boiling organic pollutants (low-boiling organic pollutants VOCs such as phenol, benzoic acid, propionic acid, etc. are mostly acidic). Triethylenetetramine is a linear small molecule that can be embedded in the micropores of ACF to adjust the micropore diameter so that the adjusted micropore size is just suitable for the adsorption of isopropanol or acetone. Compared with the use of water-soluble polyamine polymers, the use of triethylenetetramine can avoid excessive steric hindrance and blocking effects on micropores, thereby reducing the problem of ACF's adsorption of low-boiling organic matter.

[0015] According to a preferred embodiment of the present invention, the mesopores and macropores in the modified activated carbon particles account for 20%-40% of the total pore volume, the sphericity is ≥0.9, the particle size is 0.1-4.0mm (preferably 1mm), and the BET specific surface area is 500-2000㎡ / g; the micropores in the modified activated carbon fiber account for more than 85% of the total pore volume, the diameter is 5-20μm, the aspect ratio is 500-2000, and the BET specific surface area is 800-3000㎡ / g; wherein, the micropore pore size is <2nm, the mesopore pore size is between 2-50nm, and the macropore pore size is >50nm. The mesopores and macropores of the modified activated carbon particles account for 20%-40%, which ensures the adsorption efficiency of the activated carbon particles for high-boiling point organic molecules. The micropores in the modified activated carbon fiber account for more than 85% of the total pore volume, which ensures its adsorption efficiency for low-boiling point small molecule organic matter.

[0016] Activated carbon particles contain a certain amount of macropores and mesopores. As the connection channel between micropores and the outside world, macropores and mesopores are very conducive to the pollution-free transmission and adsorption of high-boiling-point organic molecules, so that the adsorption sites of activated carbon particles are fully utilized. However, the adsorption of low-boiling-point organic molecules by activated carbon particles will be competed with the adsorption of high-boiling-point organic gas molecules, resulting in the weak adsorption of low-boiling-point organic gas molecules by activated carbon particles. More than 95% of the pores in activated carbon fibers are micropores, which can firmly absorb low-boiling-point organic pollutants.

[0017] According to a preferred embodiment of the present invention, the modification steps of the activated carbon particles are as follows:

[0018] (1) Wash the activated carbon particles with deionized water and dry them;

[0019] (2) immersing the dried activated carbon particles in a 65-75% phosphoric acid solution at a solid-liquid volume ratio of 1:1.5-3, and treating at 80-100°C for 1-2 hours; separating the activated carbon particles, washing with water and drying, and then transferring to a 1-3% tannic acid solution, stirring and treating at 60-90°C for 1-3 hours; cooling to room temperature after the treatment, separating the activated carbon particles, washing with water until neutral, and drying;

[0020] (3) Putting the activated carbon particles into an ethanol solution of a silane coupling agent with a concentration of 1-4%, stirring and reacting in a constant temperature water bath at 50-80° C. for 2-4 hours, so that the silane coupling agent is grafted onto the surface of the activated carbon particles; separating the activated carbon particles, washing with ethanol and drying to obtain the activated carbon particles.

[0021] Treating activated carbon particles with a 65-75% phosphoric acid solution can both increase the porosity of activated carbon particles (adjust the proportion of macropores and mesopores) and prevent the collapse of the activated carbon particle structure. Lower concentrations of phosphoric acid have a poor effect on adjusting the porosity, while too high a phosphoric acid concentration can easily lead to the collapse of the activated carbon particle structure. Tannic acid is a polyphenolic compound that can chemically bond with the surface of activated carbon, increase the active sites on the surface, and has good antioxidant properties, which can improve the stability and service life of activated carbon.

[0022] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane and / or γ-aminopropyltrimethoxysilane. The silane coupling agent is a hydrophobic silane coupling agent, which is more likely to adsorb high-boiling point organic pollutant gas molecules (most high-boiling point organic pollutant gas molecules are hydrophobic).

[0023] According to a preferred embodiment of the present invention, the modification method of activated carbon fiber is as follows:

[0024] (1) Clean the activated carbon fiber with deionized water and dry it;

[0025] (2) placing the activated carbon fiber in a 1-5% aqueous solution of ammonium persulfate and reacting it at room temperature for 2-4 hours; taking it out, washing it with water until it is neutral, and drying it;

[0026] (3) putting the activated carbon fiber into an ethanol solution of epichlorohydrin with a concentration of 8-15%, stirring and reacting at 50-80° C. for 2-4 hours, taking it out, washing it with ethanol, and drying it;

[0027] (4) The activated carbon fiber is placed in a 4-7% aqueous solution of triethylenetetramine, stirred at 50-80°C for 2-4 hours, taken out, washed with water, and dried to obtain the product. Triethylenetetramine does not undergo obvious self-polymerization at temperatures below 100°C, but it also undergoes self-polymerization to a certain extent, and produces linear molecules of polyamine or polyimide groups, which can be easily embedded in the micropores of ACF to adjust the pore size.

[0028] In actual production, the activated carbon fiber can be modified first and then made into non-woven fabric or 100% activated carbon fiber felt with other synthetic fibers. Alternatively, the activated carbon fiber can be first made into non-woven fabric or 100% activated carbon fiber felt with other synthetic fibers and then modified according to the modification method of activated carbon fiber. The latter is preferred. Commercial non-woven fabric or activated carbon fiber felt containing activated carbon fibers can be directly purchased and then modified according to the method of the present invention.

[0029] According to a preferred embodiment of the present invention, after the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are prepared separately, the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are combined into one by sewing.

[0030] The stitching method is adopted to avoid the problem of increased air resistance and poor adsorption efficiency caused by partial pore blockage of the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer by the glue. The thickness of each functional layer can be set as needed. For example, it can be set accordingly according to the ratio of high molecular organic matter and small molecular organic matter in organic pollutants.

[0031] According to a preferred embodiment of the present invention, the activated carbon fiber adsorption functional layer includes at least one layer of non-woven fabric blended with synthetic fibers and activated carbon fibers, or the activated carbon fiber adsorption functional layer is an activated carbon fiber felt of 100% activated carbon fibers, or a composite structure composed of a synthetic fiber non-woven fabric and activated carbon fiber felt; the synthetic fiber is PEI, PET, PP, PAN, PA, PU or viscose fiber; the mass proportion of synthetic fibers in the activated carbon fiber adsorption functional layer is 15-40%.

[0032] Preferably, when PEI is used, since PEI has abundant amine groups, it can also provide additional adsorption capacity, so that the organic molecules are adsorbed, slowed down or retained.

[0033] Compared with 100% activated carbon fiber felt, non-woven fabrics containing synthetic fibers have better toughness, bending resistance and mechanical properties, can be pleated multiple times, and have better overall stability. Activated carbon fiber felt also has a certain degree of flexibility, but its mechanical properties are not as good as the former. Activated carbon fiber felt is prone to fiber breakage or loose structure during multiple bending and use. In the present invention, selection can be made according to actual needs. For example, when the requirements for bending resistance and mechanical properties are not high, 100% activated carbon fiber felt can be used to increase the adsorption capacity of the composite filter medium for low-boiling organic matter. In situations where the bending performance and mechanical properties are required to be high, synthetic fibers and activated carbon fibers can be blended to form non-woven fabrics or synthetic fiber non-woven fabrics can be composited with activated carbon fiber felt (which can be pressed). Both methods can increase the mechanical properties of the activated carbon fiber adsorption functional layer. Preferably, the activated carbon fiber is made of one or more of phenolic-based fibers, PAN-based fibers, and viscose-based fibers that are carbonized at high temperature.

[0034] According to a preferred embodiment of the present invention, the activated carbon particle adsorption functional layer comprises at least one layer of carbon cloth, which is composed of a non-woven fabric substrate and modified activated carbon particles composited on the non-woven fabric substrate; the modified activated carbon particles are at least one of modified wood activated carbon, modified coconut shell activated carbon, modified fruit shell activated carbon and modified coal activated carbon; the gram weight of the non-woven fabric substrate is 15-150g / m 2 , thickness is 0.1-1mm, air permeability is 50-500mm / s. Coconut shell activated carbon has a very high specific surface area (≥1000m 2 / g), with a large number of micropores inside. The coconut shell activated carbon has a variety of functional groups on its surface, such as hydroxyl (-OH), carboxyl (-COOH) and carbonyl (=O), etc. These characteristics enhance the adsorption capacity. Coconut shell activated carbon has high mechanical strength, is not easy to break, can maintain a good shape, and reduce the generation of dust. After phosphoric acid modification, a large number of micropores and mesopores can be formed in coconut shell activated carbon, further increasing the specific surface area and adsorption sites.

[0035] According to a preferred embodiment of the present invention, the preparation method of the carbon cloth is: uniformly applying glue (hot melt glue) on the non-woven fabric substrate, uniformly spreading the modified activated carbon particles on the non-woven fabric substrate, pressing at 0.5-2MPa to complete the composite of the modified activated carbon particles and the non-woven fabric substrate; after purging, filling the blank space according to the aforementioned method according to the blank space situation; or

[0036] The non-woven fabric substrate is a fiber containing a low-thermofusible polymer material. The heating conditions are controlled to soften the low-thermofusible polymer material of the non-woven fabric but not to fluidize. At this time, the modified activated carbon particles are evenly spread on the non-woven fabric substrate and pressed at 0.5-3MPa to complete the compounding of the modified activated carbon particles and the non-woven fabric substrate.

[0037] Among them, controlling the heating conditions so that the low-thermal-melting polymer material of the non-woven fabric softens and does not fluidize means that the temperature is between the glass transition temperature (Tg) and the melting point (Tm) of the material and is close to Tm, which can not only press and bond the activated carbon particles with the help of external force, but also prevent the hot-melt polymer from flowing and blocking the pores of the non-woven fabric and the activated carbon. During the pressing process, the activated carbon particles can also form a chemical coupling with the non-woven fabric material using the groups of the silane coupling agent on its surface. Preferably, the melting point of the low-thermal-melting polymer material is lower than 170°C. Preferably, a low-thermal-melting polymer material such as polyethylene terephthalate (PBT) or polycaprolactone (PCL) can be mixed with a small amount of PBT and PCL (melting point at 110-150°C) in the PET non-woven fabric to obtain PET fibers containing low-thermal-melting polymer materials; in addition, PP fibers and ES fibers (composed of polypropylene (PP) and polyester (PET), in a parallel or skin-core structure) added with PCL are fibers containing low-thermal-melting polymer materials.

[0038] According to a preferred embodiment of the present invention, the activated carbon particle adsorption functional layer includes more than two layers of carbon cloth, and each layer of carbon cloth is overlapped along the flow direction of the wind. When overlapping, the average pore size of the modified activated carbon particles is gradually reduced (or the total proportion of macropores and mesopores is reduced) in the direction from the air inlet side to the air outlet side. For example, the first layer is close to the air inlet side, and the second and third layers are close to the air outlet side in turn. In the first layer, the micropores of the modified activated carbon particles account for 60%, the mesopores account for 28%, and the macropores account for 12%; in the second layer, the micropores of the modified activated carbon particles account for 70%, the mesopores account for 20%, and the macropores account for 10%; in the third layer, the micropores of the modified activated carbon particles account for 74%, the mesopores account for 18%, and the macropores account for 8%.

[0039] Through the arrangement of the activated carbon particles with the above-mentioned stepped pore size, small organic molecules with molecular weights ranging from large to small can be adsorbed in sequence and in an orderly manner, thereby preventing the adsorption competition and adsorption inhibition of low-boiling point organic molecules by high-boiling point and relatively high-boiling point organic molecules.

[0040] According to a preferred embodiment of the present invention, in order to reduce the use of glue in the composite process and avoid the glue wrapping the modified activated carbon particles to cause the macropores and mesopores thereof to be blocked, the preparation method of the carbon cloth is as follows:

[0041] (1) dispersing non-woven fabric fibers in water or an organic solvent to form a uniform first suspension, and dividing the suspension into two parts; transferring the first suspension into a suction filtration device, and forming a first layer of mesh fabric on a porous support by vacuum suction;

[0042] (2) dispersing the modified activated carbon particles and the non-woven fabric fibers in water or an organic solvent to form a uniform second suspension, transferring the suspension into a suction filtration device, and depositing the activated carbon particles on the first mesh cloth by vacuum suction; the concentration of the non-woven fabric fibers in the second suspension is 1 / 10-1 / 20 of the concentration of the non-woven fabric fibers in the first suspension;

[0043] (3) Then, the second suspension is transferred to a suction filtration device, and the non-woven fabric fibers are formed into a second layer of mesh on the porous support by vacuum suction; the first layer of mesh and the second layer of mesh integrally encapsulate the modified activated carbon particles therein; and mechanical pressing is performed to obtain a carbon cloth. The organic solvent may be ethanol or isopropanol.

[0044] The above-mentioned layered wet-laid method allows the activated carbon particles to be firmly sandwiched between two layers of non-woven fabrics, and does not use any film-forming adhesives, thereby avoiding the problem that the adhesive blocks the macropores or mesopores of the activated carbon particles, resulting in a significant decrease in their adsorption efficiency. When depositing the activated carbon particles, a small amount of non-woven fabric fibers are used to make the carbon particles deposit more evenly, so that the activated carbon particles are covered more evenly on the first layer of mesh cloth to avoid local accumulation. The carbon cloth prepared by this method can better retain the air permeability of the non-woven fabric, reduce air resistance, and give full play to the adsorption efficiency of the activated carbon particles.

[0045] The organic solvent may be at least one of ethanol, isopropanol, tetrahydrofuran, dimethylformamide, N,N-dimethylacetamide, cyclohexanone and dichloromethane.

[0046] In a second aspect, the present invention relates to a composite filter medium for removing low-boiling point organic matter prepared by the above method.

[0047] Preferably, the activated carbon particle adsorption functional layer has a gram weight of 500-2000 g / ㎡, a thickness of 1-5 mm, and a pressure difference of 30-300 Pa@0.45 m / s;

[0048] The activated carbon fiber adsorption functional layer has a gram weight of 200-1000g / ㎡, a thickness of 1-5mm, and a pressure difference of 20-250Pa@0.45m / s.

[0049] (III) Beneficial effects

[0050] The composite filter medium of the present invention uses carbon cloth with activated carbon particles on its air inlet side and activated carbon fiber felt or non-woven fabric containing activated fibers on the air outlet side. The activated carbon particles have a higher adsorption firmness for high boiling points, and the activated carbon fibers have a greater adsorption firmness for low boiling points. The composite filter medium of the present invention can use the carbon cloth to adsorb most of the high boiling point organic gas molecules, while the low boiling point molecules are more adsorbed by the activated carbon fibers. Compared with the prior art, the present invention uses activated carbon particles to first fix the high boiling point organic matter, which can avoid the adsorption competition and adsorption inhibition problems of high boiling point organic molecules on low boiling point organic molecules.

[0051] The composite filter medium of the present invention uses different reagents and methods to modify the activated carbon particles and activated carbon fibers respectively. The activated carbon particles are modified by phosphoric acid, tannic acid and low-polarity coupling agent in sequence. Phosphoric acid can adjust the pore structure of the activated carbon particles and increase the proportion of mesopores and macropores on the activated carbon particles. Tannic acid can add a large number of active hydroxyl groups on the activated carbon particles and improve the stability of the activated carbon particles. The silane coupling agent is then used for modification, which is conducive to enhancing the adsorption effect of the activated carbon particles on high-boiling point molecules. The activated fiber is modified by a linear molecule (triethylenetetramine) with rich amine groups, so that the activated carbon fiber is easier to adsorb low-boiling point organic matter. Triethylenetetramine can be embedded in the micropores of the activated carbon fiber, and the size of the micropores is adjusted so that the adjusted micropore size is just suitable for the adsorption of isopropanol or acetone. Compared with the modification using water-soluble polyamine polymer molecules, the use of triethylenetetramine can avoid the problem of causing excessive steric hindrance and blocking of micropores, thereby reducing the adsorption capacity of ACF for low-boiling point organic matter.

[0052] The composite filter medium of the present invention is particularly suitable for purifying air in semiconductor manufacturing workshops, and can effectively filter small molecular organic matter, especially low-boiling point organic matter commonly found in the air of semiconductor production workshops, such as isopropanol, acetone, ethyl acetate, 1,2-dichloroethane, etc., and has excellent removal effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is a schematic diagram of the structure of the carbon cloth in the composite filter medium of the present invention.

[0054] Figure 2 It is a schematic diagram of the structure of the modified activated carbon fiber felt in the composite filter medium of the present invention.

[0055] Figure 3 It is a schematic diagram of the folded state of the composite filter medium of the present invention in the air filter.

[0056] Figure 4 The figure is a schematic diagram of the structure of an air filter including the composite filter medium of the present invention.

[0057] Figure 5 The adsorption attenuation curves of the filter media prepared in Example 1, Examples 4-5 and Comparative Examples 1-3.

[0058] Explanation of reference numerals: 111 - carbon cloth; 11 - activated carbon particle adsorption functional layer; 121 - carbon fiber cloth; 12 - activated carbon fiber adsorption functional layer; 10 - composite filter medium; 20 - air filter; 21 - mounting frame; 22 - wire mesh. DETAILED DESCRIPTION

[0059] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. In the examples of the present application, unless otherwise specified, % refers to mass percentage concentration.

[0060] like Figure 1 The carbon cloth 111 is a schematic diagram of the structure. The carbon cloth 111 is used to form an activated carbon particle adsorption functional layer 11. The activated carbon particle adsorption functional layer 11 is composed of at least one layer of carbon cloth 111. Figure 2 The carbon fiber cloth 121 is a schematic structural diagram. The carbon fiber cloth 121 is used to form an activated carbon fiber adsorption functional layer 12. The activated carbon fiber adsorption functional layer 12 is composed of at least one layer of carbon fiber cloth 121. Figure 3 The figure shows a schematic diagram of the folded state of the composite filter medium 10 of the present invention, wherein the outer layer (towards the air inlet side) is an activated carbon particle adsorption functional layer 11, and the inner layer (towards the air outlet side) is an activated carbon fiber adsorption functional layer 12. The activated carbon particle adsorption functional layer 11 and the activated carbon fiber adsorption functional layer 12 are composited into a sheet material, and then folded into folds of a certain width (the fold width in each example below is 15 cm), and then installed in a manner of folding into a plurality of folds. Figure 4 In the air filter 20 shown in FIG. 1 , the air filter 20 includes a mounting frame 21, the composite filter medium 10 is mounted in the mounting frame 21, and protective metal meshes 22 are respectively provided on the air inlet side and the air outlet side of the composite filter medium 10. Figure 4 .

[0061] Example 1

[0062] This embodiment provides a method for preparing a composite filter medium for removing low-boiling point organic matter, wherein the composite filter medium comprises an air inlet side adsorption layer and an air outlet side adsorption layer, wherein an activated carbon particle adsorption functional layer is arranged on the air inlet side, and an activated carbon fiber adsorption functional layer is arranged on the air outlet side adsorption layer. The method for preparing the composite filter medium is as follows:

[0063] (I) Preparation of activated carbon particle adsorption functional layer

[0064] (1) The coconut shell activated carbon particles were cleaned with deionized water and dried in an oven at 80°C; the dried activated carbon particles were immersed in a 70% phosphoric acid solution at a solid-liquid volume ratio of 1:2, and stirred at 90°C for 1h; the activated carbon particles were separated, rinsed with water and dried, and then transferred to a 2% tannic acid solution and stirred at 70°C for 1h; after the treatment, they were cooled to room temperature, the activated carbon particles were separated, washed with water until neutral, and dried in an oven at 80°C. The activated carbon particles were then immersed in a 2% γ-aminopropyltriethoxysilane ethanol solution, stirred in a constant temperature water bath at 50°C for 4h, the activated carbon particles were separated, washed with ethanol, and dried in an oven at 80°C to obtain modified activated carbon particles. The average particle size of the modified activated particles was 1mm, the ratio of the mesopores and macropores to the total pore volume of the modified activated particles was 38%, the sphericity was ≥0.9, and the BET was 1500㎡ / g.

[0065] (2) Select a weight of 90g / m 2 , a non-woven fabric substrate (PP non-woven fabric) with a thickness of 0.8 mm and an air permeability of 300 mm / s. Hot melt adhesive (epoxy acrylate) is evenly applied on the non-woven fabric substrate, and the modified activated carbon particles prepared in step (1) are evenly spread on the non-woven fabric substrate, and pressed at 0.5 MPa to complete the composite of the modified activated carbon particles and the non-woven fabric substrate; after purging, the blank space is filled according to the above method according to the blank space situation to obtain a carbon cloth.

[0066] (3) The two layers of carbon cloth are stacked, and a non-woven fabric substrate identical to that in step (2) is covered on the outside to cover the modified activated carbon particles on the inside, thereby obtaining the activated carbon particle adsorption functional layer. The activated carbon particle adsorption functional layer has a gram weight of 1600 g / ㎡, a thickness of 3.5 mm, and a pressure difference of 100 Pa@0.45 m / s.

[0067] (II) Preparation of activated carbon fiber adsorption functional layer

[0068] (1) A non-woven fabric containing 30% PAN fiber (polyacrylonitrile fiber) and 70% activated carbon fiber is cleaned with deionized water and dried in an oven; the dried non-woven fabric is put into an aqueous solution of ammonium persulfate with a concentration of 2% (mass concentration) and reacted at room temperature for 3 hours; after being taken out, it is washed with water until neutral and dried in an oven; the non-woven fabric is put into an ethanol solution of epichlorohydrin with a concentration of 10%, stirred and reacted at 60°C for 2 hours, taken out and drained, washed with ethanol, and dried in an oven; then put into an aqueous solution of 5% triethylenetetramine, stirred and reacted at 60°C for 2 hours, taken out, rinsed with deionized water, and dried in an oven to obtain a non-woven fabric containing modified activated carbon fibers.

[0069] (2) A double layer of non-woven fabric containing modified activated carbon fiber is stacked to form an activated carbon fiber adsorption functional layer. The activated carbon fiber is obtained by high-temperature carbonization of PAN-based fiber. The micropores in the activated carbon fiber account for 90% of the total pore volume, the diameter is 5-20μm, the aspect ratio is 500-2000, and the BET specific surface area is about 2100㎡ / g. The activated carbon fiber adsorption functional layer has a gram weight of 500g / ㎡, a thickness of 3mm, and a pressure difference of 100Pa@0.45m / s.

[0070] (III) After the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are formed into appropriate sizes, the activated carbon particle adsorption functional layer is placed on the air inlet side, and the activated carbon fiber adsorption functional layer is placed on the air outlet side. The activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are composited together by interval stitching, slightly flattened and expanded to obtain a composite filter medium, and then pressed Figure 3 Folding method, and Figure 4 Install it in the air filter.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that when preparing the activated carbon particle adsorption functional layer, the modification conditions of the activated carbon particles are different, specifically: the coconut shell activated carbon particles (the raw materials are the same as those in embodiment 1) are cleaned with deionized water and dried; the dried activated carbon particles are immersed in a 65% phosphoric acid solution according to a solid-liquid volume ratio of 1:2, and stirred at 90°C for 1.5 hours; the activated carbon particles are separated, rinsed with water and dried, and then transferred to a 3% tannic acid solution, stirred at 80°C for 2 hours; after the treatment, the activated carbon particles are cooled to room temperature, the activated carbon particles are separated, washed with water until neutral, and dried. The activated carbon particles are then immersed in a 3% γ-aminopropyltrimethoxysilane ethanol solution, stirred in a constant temperature water bath at 80°C for 2 hours, the activated carbon particles are separated, washed with ethanol, and dried to obtain modified activated carbon particles. The average particle size of the modified active particles is 1 mm, the mesopores and macropores of the modified active particles account for 32% of the total pore volume, the sphericity is ≥0.9, and the BET is 1570 m2 / g.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is that the preparation method of the carbon cloth is different when preparing the activated carbon particle adsorption functional layer. Specifically,

[0075] Modified activated carbon particles were prepared according to the method of Example 1, and then the weight of the particles was 100 g / m 2, a non-woven fabric substrate with a thickness of 0.8mm and an air permeability of 310mm / s, and the non-woven fabric substrate is a PP fiber non-woven fabric with PCL added. Control the heating conditions to uniformly heat the non-woven fabric substrate to 130°C. At this time, the modified activated carbon particles are evenly spread on the non-woven fabric substrate and pressed at 2MPa to complete the compounding of the modified activated carbon particles and the non-woven fabric substrate to obtain carbon cloth. The two layers of carbon cloth are overlapped and covered with the same non-woven fabric substrate on the outside to obtain an activated carbon particle adsorption functional layer. The activated carbon particle adsorption functional layer has a gram weight of 1500g / ㎡, a thickness of 3.4mm, and a pressure difference of 96Pa@0.45m / s.

[0076] Example 4

[0077] The difference between this embodiment and embodiment 1 is that the preparation method of the carbon cloth is different when preparing the activated carbon particle adsorption functional layer. Specifically,

[0078] Modified activated carbon particles were prepared according to the method of Example 1, and carbon cloth was prepared by wet web forming method. The specific process was as follows: ① PP fibers were dispersed in water at 0.5% (mass concentration) to form a uniform first suspension, and the suspension was divided into two parts; the first suspension was transferred to a suction filtration device, and the non-woven fibers were formed into a first layer of mesh on a porous support by vacuum suction. ② The modified activated carbon particles and PP fibers prepared in Example 1 were dispersed in water to form a uniform second suspension (wherein the concentration of activated carbon particles was 1.5% and the concentration of PP fibers was 0.05%), which was transferred to a suction filtration device, and the activated carbon particles were deposited on the first layer of mesh by vacuum suction; ③ Then, the second suspension was transferred to a suction filtration device, and the non-woven fibers were formed into a second layer of mesh on a porous support by vacuum suction; the first layer of mesh and the second layer of mesh integrally encapsulated the modified activated carbon particles; mechanical pressing was performed to obtain carbon cloth. ④ The two layers of carbon cloth were overlapped to obtain an activated carbon particle adsorption functional layer. The activated carbon particle adsorption functional layer has a gram weight of 1711g / ㎡, a thickness of 4mm, and a pressure difference of 121Pa@0.45m / s.

[0079] Example 5

[0080] The difference between this embodiment and embodiment 1 is that the preparation method of the activated carbon particle (ACG) adsorption functional layer is different, specifically:

[0081] The coconut shell activated carbon particles were modified according to the method of Example 1, except that activated carbon particles of different specifications were used as raw materials. After modification, two modified activated carbon particles were obtained. The first modified activated carbon particles had a micropore ratio of 62%, a mesopore ratio of 26%, and a macropore ratio of 12%. The second modified activated carbon particles had a micropore ratio of 70%, a mesopore ratio of 20%, and a macropore ratio of 10%. The average particle size of the two modified activated particles was 1 mm. According to the preparation method of the carbon cloth in Example 1, a carbon cloth with a gram weight of 100 g / m 2 , a non-woven fabric substrate (PP non-woven fabric) with a thickness of 0.8mm and an air permeability of 300mm / s. Hot melt adhesive (epoxy acrylate) is evenly applied on the non-woven fabric substrate, and the two modified activated carbon particles are evenly spread on the non-woven fabric substrate, and pressed at 0.5MPa to obtain the first and second layers of carbon cloth. The first layer of carbon cloth uses the first modified activated carbon particles, and the second layer of carbon cloth uses the second modified activated carbon particles. The two layers of carbon cloth are overlapped, with the first layer of carbon cloth facing the air inlet side and the second layer of carbon cloth opposite to the air inlet side. After covering the outside with the same non-woven fabric substrate, the activated carbon particle adsorption functional layer is obtained. The activated carbon particle adsorption functional layer has a gram weight of 1500g / ㎡, a thickness of 3.6mm, and a pressure difference of 111Pa@0.45m / s.

[0082] Example 6

[0083] The difference between this embodiment and embodiment 1 is that the preparation method of the activated carbon fiber adsorption functional layer is different, specifically:

[0084] (1) Clean the 100% activated carbon fiber felt with deionized water and dry it in an oven; put the dried activated carbon fiber felt into an aqueous solution of ammonium persulfate with a concentration of 2.5% (mass concentration) and react at room temperature for 2 hours; after taking it out, wash it with water until it is neutral and dry it in an oven; put the activated carbon fiber felt into an ethanol solution of epichlorohydrin with a concentration of 12%, stir and react at 60°C for 2 hours, take it out and drain it, wash it with ethanol, and dry it in an oven; then put it into a 4% aqueous solution of triethylenetetramine, stir and react at 60°C for 2 hours, take it out, rinse it with deionized water, and dry it in an oven to obtain modified activated carbon fiber felt. (2) Stack two layers of modified activated carbon fiber felt to form an activated carbon fiber adsorption functional layer. Among them, the activated carbon fiber is obtained by high-temperature carbonization of PAN-based fiber. The activated carbon fiber adsorption functional layer has a gram weight of 608g / ㎡, a thickness of 4.1mm, and a pressure difference of 119Pa@0.45m / s.

[0085] In the above Examples 2-6, the parts not specially explained, including the combination of the two adsorption functional layers, the selection of raw materials for preparing the adsorption functional layers, the preparation process operation, the folding of the composite filter medium and the installation of the air filter, are all carried out in accordance with the method of Example 1.

[0086] In order to compare the removal capacity of low-boiling organic molecules by filter media prepared by different preparation methods, the following comparative examples were obtained by changing some preparation methods and operating conditions during the preparation of the composite filter media of the above embodiments. In the following comparative examples, if there is no special explanation, the raw material selection, preparation operation and filter installation are all carried out with reference to Example 1.

[0087] Comparative Example 1

[0088] In this comparative example, two activated carbon particle (ACG) adsorption functional layers prepared in Example 1 were stacked and composited with a stainless steel frame (the composite method was the same as that in Example 1) to obtain an air filter medium without activated carbon fibers.

[0089] Comparative Example 2

[0090] In this comparative example, two activated carbon fiber (ACF) adsorption functional layers prepared in Example 1 were stacked and composited with a stainless steel frame (the composite method was the same as that in Example 1) to obtain an air filter medium without activated carbon particles ACG.

[0091] Comparative Example 3

[0092] In this comparative example, the arrangement order of the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer is changed, the activated carbon fiber adsorption functional layer is placed on the air inlet side, and the activated carbon particle adsorption functional layer is placed on the air outlet side, to prepare a composite filter medium.

[0093] Comparative Example 4

[0094] In this comparative example, when preparing the activated carbon fiber adsorption functional layer in Example 1, a non-woven fabric containing 30% PAN fiber (polyacrylonitrile fiber) and 70% activated carbon fiber is used as the raw material, but the "5% triethylenetetramine aqueous solution" used to modify the activated carbon fiber is replaced with an equal concentration of hyperbranched terminal amino HPAMAM (molecular weight of 4000, branching degree of 0.4, total amine value of 0.068 mol / g) aqueous solution. After the modification is completed, take it out, rinse with deionized water, and dry in an oven to obtain a non-woven fabric containing modified activated carbon fibers. Double layers of non-woven fabrics containing modified activated carbon fibers are stacked to form an activated carbon fiber adsorption functional layer.

[0095] Comparative Example 5

[0096] In this comparative example, when preparing the activated carbon fiber adsorption functional layer in Example 1, a non-woven fabric containing 30% PAN fiber (polyacrylonitrile fiber) and 70% activated carbon fiber blended is used as the raw material. However, during the modification process, "10% epichlorohydrin and 5% triethylenetetramine are co-dispersed in water" to obtain a mixed solution, and the non-woven fabric is modified using the mixed solution. The mixture is stirred and reacted at 60°C for 2 hours, and then taken out, rinsed with deionized water, and dried in an oven to obtain a non-woven fabric containing modified activated carbon fibers. Double layers of non-woven fabric containing modified activated carbon fibers are stacked to form an activated carbon fiber adsorption functional layer.

[0097] Comparative Example 6

[0098] In this comparative example, when preparing the activated carbon particle adsorption functional layer in Example 1, the step of using the γ-aminopropyltriethoxysilane ethanol solution for modification is not included.

[0099] Filter media performance testing

[0100] (I) Filter media were prepared in Examples 1-6 and Comparative Examples 1-6, respectively, and recorded as A1, A2, A3, A4, A5, A6, D1, D2, D3, D4, D5, and D6 in sequence. The filter media prepared in the aforementioned Examples and Comparative Examples were placed in the AMC test system for air purification efficiency testing, with a test temperature of 23±2°C, a test humidity of 50±2%, a surface wind speed of 0.50 m / s, and challenging gas molecules were added to the air inlet side. The air was blown continuously for 1 hour to eliminate interfering substances in the detection air duct, and then a Tenax-GR tube was used to take samples and the concentration of challenging gas molecules in the air outlet side was analyzed by GC-MS to obtain the initial removal rate.

[0101] During the test, the initial concentrations of some organic molecules added to the air inlet side are as follows (concentration unit is ppbv, 1ppbv = 1nL / L): isopropyl alcohol (IPA, boiling point 82.6℃), 3.12; acetone (ACN, boiling point 56.5℃), 5.64; ethyl acetate (EA, boiling point 77.1℃), 1.41; 1,2-dichloroethane (DCE, boiling point 83.5℃), 0.26; trifluorotoluene (TFT, 120℃), 10.39; toluene (TOL, boiling point 110.6℃), 1.09; butyl acetate (BA, 126.1℃), 0.90; p-xylene (p-XYL, 138.4℃), 0.48; alkanes, 6.23. TVOC (total volatile organic matter is the sum of the above organic molecules and a small amount of other organic molecules), 31.89. The concentrations of various organic molecules on the air outlet side are shown in Table 1.

[0102] Table 1: Organic matter molecule concentration on the air outlet side of the filter media of each embodiment and comparative example

[0103] Group IPA ACN EA DCE TFT TOL BA p-XYL Alkanes TVOC Removal rate % A1 0.34 0.55 <0.10 <0.10 0.61 <0.10 <0.10 <0.10 0.39 0.99 96.89 A2 0.31 0.50 <0.10 <0.10 0.64 <0.10 <0.10 <0.10 0.38 1.04 96.74 A3 0.30 0.48 <0.10 <0.10 0.59 <0.10 <0.10 <0.10 0.36 0.94 97.05 A4 0.24 0.41 <0.10 <0.10 0.52 <0.10 <0.10 <0.10 0.28 0.85 97.33 A5 0.22 0.38 <0.10 <0.10 0.44 <0.10 <0.10 <0.10 0.25 0.74 97.68 A6 0.28 0.47 <0.10 <0.10 0.62 <0.10 <0.10 <0.10 0.40 0.99 96.89 D1 0.63 0.87 0.23 0.17 0.64 <0.10 <0.10 <0.10 0.38 2.45 92.31 D2 0.51 0.69 0.14 0.13 1.56 0.32 0.21 0.22 0.60 3.08 90.34 D3 0.50 0.67 0.12 0.11 0.83 0.15 0.14 0.12 0.42 2.29 92.82 D4 0.58 0.74 0.16 <0.10 0.65 0.11 <0.10 <0.10 0.40 1.86 94.17 D5 0.55 0.70 0.12 <0.10 0.61 0.12 0.10 <0.10 0.41 1.77 94.45 D6 0.51 0.66 0.14 <0.10 0.74 0.30 0.18 <0.10 0.46 2.02 93.67

[0104] Removal rate % is the initial removal rate of the filter medium, initial removal rate = (TVOC on the air inlet side - TVOC on the air outlet side) / TVOC on the air inlet side × 100%;

[0105] It can be seen from the above table that the composite filter medium prepared by the present invention can effectively remove low-boiling-point and high-boiling-point organic pollutant molecules such as isopropanol, acetone, ethyl acetate, 1,2-dichloroethane, trifluorotoluene, toluene, butyl acetate, p-xylene, and alkanes in the air, and can significantly reduce the TVOC value in the air.

[0106] Among all the embodiments, the composite filter media prepared in Embodiments 4-5 has the best effect on removing organic pollutant molecules in the air, followed by Embodiments 3 and 6. The process of preparing the carbon cloth in Embodiment 3 retains more pores, so that its removal efficiency is better. The process of preparing the carbon cloth in Embodiment 4 maximizes the adsorption activity of the activated carbon particles; in Embodiment 5, two modified activated carbon particles with different pore size specifications are used when preparing the composite carbon cloth to achieve graded adsorption of organic pollutant molecules in the air, further increasing the adsorption efficiency of the activated carbon particles. In Embodiment 6, 100% activated carbon fiber felt is used when preparing the activated carbon fiber adsorption functional layer, which improves the adsorption and removal of low-boiling point molecules such as IPA and ACN, and has no obvious effect on the adsorption of high-boiling point molecules.

[0107] Comparison between Example 1 and Comparative Examples 1-2 shows that when the filter medium uses only carbon cloth or activated carbon fiber as an adsorption material, the removal capacity of the filter medium for low-boiling point organic matter and high-boiling point organic matter molecules in the air is reduced. Comparison between Example 1 and Comparative Example 3 shows that when the air inlet side of the filter medium uses an activated carbon fiber adsorption functional layer and the air outlet side uses an activated carbon particle adsorption functional layer, although the organic molecules on the air outlet side are significantly reduced, the ideal removal effect cannot be achieved.

[0108] It can be seen from Example 1 and Comparative Example 4 that when the activated carbon fiber (or non-woven fabric containing activated carbon fiber) is modified, if the triethylenetetramine molecule is replaced with a water-soluble polyamine polymer molecule, the adsorption efficiency of the activated carbon fiber for low-boiling point small molecules such as IPA, ACN and EA will decrease. It can be seen from Example 1 and Comparative Example 5 that if the activated carbon fiber is modified by a mixed system of epichlorohydrin / triethylenetetramine, the adsorption efficiency of the activated carbon fiber for low-boiling point small molecules such as IPA, ACN and EA will also decrease. This shows that the use of water-soluble polyamine (or imine) polymer molecules to modify the activated carbon fiber is prone to excessive adjustment of the size of the activated carbon fiber micropores (the micropore size is too small or blocked), and the steric hindrance is large, so that the adsorption efficiency of the adjusted activated carbon fiber micropores for low-boiling point organic molecules decreases. Epichlorohydrin / triethylenetetramine is prone to polymerization to form a network structure, which also leads to the blocking of the activated carbon fiber micropores and large steric hindrance.

[0109] From the comparison between Example 1 and Comparative Example 6, it can be seen that when phosphoric acid and tannic acid are used to modify the activated carbon particles, no further modification with a hydrophobic silane coupling agent will be used, which will reduce the removal efficiency of the prepared composite filter medium for high-boiling point organic molecules, and further affect the adsorption effect of the entire composite filter medium for low-boiling point molecules. This is mainly because the polarity of the activated carbon particles is increased after modification with phosphoric acid and tannic acid. If no further modification with a hydrophobic silane coupling agent is used, it will be unfavorable for the activated carbon particles to adsorb non-polar organic molecules such as alkanes.

[0110] (ii) Testing the adsorption attenuation of filter media in the AMC test system

[0111] The filter media prepared in Example 1, Example 4, Example 5, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were subjected to an adsorption performance attenuation test. During the test, the environmental conditions and the concentration of the challenging organic gas molecules added were the same as in (I). During the test, samples were taken every 30 minutes to test the TVOC on the air outlet side and the removal rate was calculated. The total monitoring time was 14 hours, and a curve of the removal rate changing with time was plotted. The experimental results are shown in FIG. Figure 5 shown.

[0112] Depend on Figure 5 It can be seen that the adsorption efficiency of the composite filter medium prepared in Example 5 for organic pollutant molecules decays the slowest, and although the initial removal rate of organic pollutant molecules in Example 4 is higher than that in Example 1, after a period of use, its removal rate of organic pollutant molecules is consistent with that in Example 1. Among the three examples, the adsorption efficiency of the composite filter medium prepared in Example 5 for organic pollutant molecules remains above 96% even after 14 hours of use.

[0113] (III) Testing the dust generation of filter media in the AMC test system

[0114] The dust generation is an indicator of the structural stability of the filter medium, and is used to detect the number of solid particles falling off the filter medium. The filter medium prepared in Example 1, Example 3, Example 4, and Example 5 was installed in a test channel, and pure air (face velocity) with a wind speed of 0.5 m / S was introduced. The concentration of solid particles (unit: f / m3) was detected downstream of the filter medium. The test was continued for 3 hours, and the test was recorded every 30 minutes. The experimental results are shown in Table 2. "~0.5 μm" in the table means that the size of the particles is between 0.3 μm and 0.5 μm.

[0115] Table 2: Dust generation of each filter medium

[0116]

[0117]

[0118] As shown in Table 3, the dust generation of the composite filter medium prepared in Example 3 is the smallest, the dust generation of the composite filter medium prepared in Example 1 and Example 5 is slightly greater than that of Example 3, and the dust generation of Example 4 is slightly greater than that of the other examples, but all meet the requirements of the production specification indicators of air filter media. Based on the above test indicators, the composite filter medium of Example 5 has the best comprehensive performance.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite filter medium for removing low-boiling point organic matter, characterized in that: The composite filter medium comprises an air inlet side adsorption layer and an air outlet side adsorption layer, wherein an activated carbon particle adsorption functional layer is arranged on the air inlet side, and an activated carbon fiber adsorption functional layer is arranged on the air outlet side adsorption layer; after the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are prepared respectively, they are compounded to obtain the composite filter medium; Among them, in the activated carbon particle adsorption functional layer, the activated carbon particles are modified activated carbon particles, and the modification method of the activated carbon particles is: pre-treating the activated carbon particles with phosphoric acid and tannic acid solutions in sequence, separating and drying, and then putting the activated carbon particles into an alcohol solution of a silane coupling agent for immersion modification, separation, and drying to obtain; Among them, in the activated carbon fiber adsorption functional layer, the activated carbon fiber is a modified activated carbon fiber, and the modification method of the activated carbon fiber is: after being treated with ammonium persulfate, the activated carbon fiber is treated with epichlorohydrin, and then the activated carbon fiber is mixed with an aqueous solution of triethylenetetramine for reaction, separated, and dried to obtain.

2. The preparation method according to claim 1, characterized in that: The modified activated carbon particles have mesopores and macropores accounting for 20%-40% of the total pore volume, sphericity ≥0.9, particle size of 0.1-4.0 mm, and BET specific surface area of ​​500-2000 m2 / g; the modified activated carbon fibers have micropores accounting for more than 85% of the total pore volume, a diameter of 5-20 μm, an aspect ratio of 500-2000, and a BET specific surface area of ​​800-3000 m2 / g; Among them, the pore size of micropores is <2nm, the pore size of mesopores is between 2-50nm, and the pore size of macropores is >50nm.

3. The preparation method according to claim 1, characterized in that: The modification method of activated carbon particles is as follows: (1) Wash the activated carbon particles with deionized water and dry them; (2) immersing the dried activated carbon particles in a 65-75% phosphoric acid solution at a solid-liquid volume ratio of 1:1.5-3, and treating at 80-100°C for 1-2 hours; separating the activated carbon particles, washing with water and drying, and then transferring to a 1-3% tannic acid solution, stirring and treating at 60-90°C for 1-3 hours; cooling to room temperature after the treatment, separating the activated carbon particles, washing with water until neutral, and drying; (3) Putting the activated carbon particles into an ethanol solution of a silane coupling agent with a concentration of 1-4%, stirring and reacting in a constant temperature water bath at 50-80° C. for 2-4 hours, so that the silane coupling agent is grafted onto the surface of the activated carbon particles; separating the activated carbon particles, washing with ethanol and drying to obtain the activated carbon particles.

4. The preparation method according to claim 3, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane and / or γ-aminopropyltrimethoxysilane.

5. The preparation method according to claim 1, characterized in that: The modification method of activated carbon fiber is as follows: (1) Clean the activated carbon fiber with deionized water and dry it; (2) placing the activated carbon fiber in a 1-5% aqueous solution of ammonium persulfate and reacting it at room temperature for 2-4 hours; taking it out, washing it with water until it is neutral, and drying it; (3) putting the activated carbon fiber into an ethanol solution of epichlorohydrin with a concentration of 8-15%, stirring and reacting at 50-80° C. for 2-4 hours, taking it out, washing it with ethanol, and drying it; (4) The activated carbon fiber is put into a 4-7% aqueous solution of triethylenetetramine, stirred and reacted at 50-80° C. for 2-4 hours, taken out, washed with water, and dried to obtain the product.

6. The preparation method according to claim 1, characterized in that: After the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are prepared separately, the activated carbon particle adsorption functional layer and the activated carbon fiber adsorption functional layer are combined into one by stitching.

7. The preparation method according to claim 1, characterized in that: The activated carbon fiber adsorption functional layer comprises at least one layer of non-woven fabric blended with synthetic fiber and activated carbon fiber, or the activated carbon fiber adsorption functional layer is an activated carbon fiber felt composed of 100% activated carbon fiber or a composite structure composed of a synthetic fiber non-woven fabric and an activated carbon fiber felt; The synthetic fiber is PEI, PET, PP, PAN, PA, PU or viscose fiber; the mass proportion of the synthetic fiber in the activated carbon fiber adsorption functional layer is 15-40%.

8. The preparation method according to claim 1, characterized in that: The activated carbon particle adsorption functional layer comprises at least one layer of carbon cloth, which is composed of a non-woven fabric substrate and modified activated carbon particles composited on the non-woven fabric substrate; the modified activated carbon particles are at least one of modified wood activated carbon, modified coconut shell activated carbon, modified fruit shell activated carbon and modified coal activated carbon; the gram weight of the non-woven fabric substrate is 15-150g / m 2 , thickness is 0.1-1mm, and air permeability is 50-500mm / s.

9. The preparation method according to claim 8, characterized in that: The carbon cloth preparation method comprises: uniformly dispensing glue on the non-woven fabric substrate, uniformly spreading the modified activated carbon particles on the non-woven fabric substrate, pressing at 0.5-2 MPa to complete the compounding of the modified activated carbon particles and the non-woven fabric substrate; after purging, filling the blank space according to the blank space situation according to the aforementioned method; or The non-woven fabric substrate is a fiber containing a low-thermofusible polymer material. The heating conditions are controlled to soften the low-thermofusible polymer material of the non-woven fabric but not to fluidize. At this time, the modified activated carbon particles are evenly spread on the non-woven fabric substrate and pressed at 0.5-3MPa to complete the compounding of the modified activated carbon particles and the non-woven fabric substrate.

10. The preparation method according to claim 8, characterized in that: The activated carbon particle adsorption functional layer includes more than two layers of carbon cloth, and each layer of carbon cloth is overlapped along the flow direction of wind. When overlapping, the average pore size of the modified activated carbon particles is gradually reduced from the wind inlet side to the wind outlet side.

11. The preparation method according to claim 8, characterized in that: The preparation method of the carbon cloth is as follows: (1) dispersing non-woven fabric fibers in water or an organic solvent to form a uniform first suspension, and dividing the suspension into two parts; transferring the first suspension into a suction filtration device, and forming a first layer of mesh fabric on a porous support by vacuum suction; (2) dispersing the modified activated carbon particles and the non-woven fabric fibers in water or an organic solvent to form a uniform second suspension, transferring the suspension into a suction filtration device, and depositing the activated carbon particles on the first mesh cloth by vacuum suction; the concentration of the non-woven fabric fibers in the second suspension is 1 / 10-1 / 20 of the concentration of the non-woven fabric fibers in the first suspension; (3) Then, the second portion of the suspension is transferred to a suction filtration device, and the non-woven fabric fibers are formed into a second layer of mesh cloth on the porous support by vacuum suction; the first layer of mesh cloth and the second layer of mesh cloth integrally encapsulate the modified activated carbon particles therein; and mechanical pressing treatment is performed to obtain a carbon cloth.

12. A composite filter medium for removing low-boiling point organic matter, characterized in that: It is prepared by the method described in any one of claims 1 to 11.

13. The composite filter medium for removing low-boiling point organic matter according to claim 12, characterized in that: The activated carbon particle adsorption functional layer has a gram weight of 500-2000g / ㎡, a thickness of 1-5mm, and a pressure difference of 30-300Pa@0.45m / s; The activated carbon fiber adsorption functional layer has a gram weight of 200-1000g / ㎡, a thickness of 1-5mm, and a pressure difference of 20-250Pa@0.45m / s.

Citation Information

Patent Citations

  • Plasma-treated adsorption filter material with protection against chemical toxins, its use and protective materials containing this adsorption filter material

    DE10356776B4

  • Filter media

    JP4589038B2